2010
DOI: 10.4065/mcp.2009.0232
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Patients' Understanding of Their Plan of Care

Abstract: OBJECTIVE:To evaluate hospitalized patients' understanding of their plan of care. PATIENTS AND METHODS:Interviews of a cross-sectional sample of hospitalized patients and their physicians were conducted from June 6 through June 26, 2008. Patients were asked whether they knew the name of the physician and nurse responsible for their care and specific questions about 6 aspects of the plan of care for the day (primary diagnosis, planned tests, planned procedures, medication changes, physician services consulted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 27 publications
4
82
1
2
Order By: Relevance
“…7,8,10 They found that agreement between physicians and nurses was greatest for procedures planned (89%) and least for discharge date (64%)-almost identical to the proportions we observed. Agreement between physicians and patients was also poor, and similar to what we observed.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…7,8,10 They found that agreement between physicians and nurses was greatest for procedures planned (89%) and least for discharge date (64%)-almost identical to the proportions we observed. Agreement between physicians and patients was also poor, and similar to what we observed.…”
Section: Discussionsupporting
confidence: 65%
“…Agreement between physicians and patients was also poor, and similar to what we observed. 8 There was no communication reported between physicians and nurses 38% of the time; agreement was not associated with reported communication but duration of communication was not measured. 7 Our study has a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we aimed to evaluate whether (1) hospital providers teach any content of these four basic self management skills ("four skills") as part of regular care to patients and their caregivers, and (2) whether information presented regarding any of the four skills' is understood and retained after the provider leaves the room. Secondarily, the project gathers information about standard or "control" care behaviors, such as hand washing on room entry or exist, [8] and quality of the provider-patient interaction [9] to capture a baseline rate for five "good clinical practice" activities.…”
Section: Introductionmentioning
confidence: 99%
“…19 With the adoption of the Accreditation Council for Graduate Medical Education (ACGME) duty hour restrictions, handoffs have increased, 20 and patients are often confused about who their physicians are and who is ''in charge.'' 21,22 While reduced hours certainly have positive consequences, residents have fewer opportunities to connect meaningfully with patients and witness the longitudinal course of illnesses. 11,12,23 Transitional and Alternate Care Settings From the ambulatory setting to hospitals, rehabilitation, extended care, and hospice facilities, transitions across care settings are moments of heightened patient vulnerability.…”
Section: The Current Reality: Discontinuities Of Carementioning
confidence: 99%